THE IMPLEMENTATION OF TEACHING SPEAKING USING RETELLING STORY TO BEGINNERS : A CASE STUDY IN SD N 1 KARANGJOHO KLATEN - Ngatinah, Ngatinah (2010)
This research aims at (1) describing the implementation of teaching speaking using retelling story at SDN 1 Karangjoho Klaten, and (2) finding the problems faced by the students and the teacher during the teaching and learning speaking skill using retelling story. In collecting the data, the writer used observation, interview, and document. This research paper is about the implementation of teaching speaking using retelling story in SDN 1 Karangjoho Klaten. Retelling story is a kind of method to develop the student's competence in vocabulary mastery, to comprehend the story, to develop their creativity to retell the story by their own words and develop their own imagination about the story. Retelling story is independent work task. The students do the task independently, based on their own competence. The results of the research show that: 1) teaching speaking using retelling story influences the students speaking master, 2) The students are very enthusiastic in learning speaking, most of them have high motivation in joining the class and great part of the students participate to be active in front of the class, and 3) Teaching speaking using retelling story is very effective